Inclusiveness of Muslim Da'wah and Entrepreneurship for Persons with Disabilities through Social Media Based on Gus Dur's Islamic Spirituality - Ilham, Moh; Santi, Mei; Aziz, Muhajir Sulthonul (Al-Muraqabah: Journal of Management and Sharia Business, 2025)
This study aims to explore the transformation of Islamic preaching and Muslim entrepreneurship practices conducted by persons with disabilities through social media, grounded in Islamic spiritual values inspired by the thoughts of KH. Abdurrahman Wahid (Gus Dur). Using a qualitative case study approach, this research focuses on three social media accounts owned by disabled Muslim entrepreneurs: @rumahaspirasitunanetra, @thisablebeautycare, and @ekosugeng. The findings reveal that social media not only serves as a communication tool but also functions as a digital preaching space and spiritual marketplace, reinforcing the role of people with disabilities as active agents of change. The participants successfully integrated Islamic values such as amanah (trustworthiness), rahmah (compassion), and maslahah (public good) into their entrepreneurial and preaching activities. These findings highlight the urgency of inclusive preaching approaches and the necessity to expand the Islamic Value-Based Entrepreneurship (IVBE) model to encompass marginalized experiences. The study concludes that spirituality-based preaching and business can be powerful strategies for social emancipation and for shaping an inclusive Islamic discourse.